PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KANTOR PERTANAHAN KABUPATEN PELALAWAN: Array - Dita Fisdian Adni; Syaprianto; Sylvina Rusadi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
PTSL is defined as the activity of registering land for the first time carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in one village / kelurahan or other name at the same level, which includes the collection of physical data and juridical data regarding one or several objects. land registration for the purposes of its registration. Seeing the low number of registered land parcels, the government is targeting to certify 5 million land parcels throughout Indonesia by 2017 through the PTSL Program. As many as 7 million land parcels in 2018, 9 million land parcels in 2019 and in 2025 all land parcels in Indonesia's territory have been registered. In accordance with the consequences of the provisions of Law Number 23 of 2014 concerning Regional Government, namely the granting of autonomy to districts one of which is in the land sector, the Land Office in each Regency / City is the implementer of the National Policy or programs in the Land Sector in the Region, one of which is Pelalawan Regency. Pelalawan Regency through its Land Office also implements this PTSL program. The purpose of carrying out this research is to see and measure the implementation of the Complete Systematic Land Registration Program at the Pelalawan Regency Land Office. The next objective is to determine the obstacles encountered by the Pelalawan Regency Land Office in implementing the Complete Systematic Land Registration Program (PTSL). The method used in this research is a qualitative research method with the type of case study research. This study uses indicators of implementation by Edward III with indicators that will be the blade of analysis, namely communication, resources, dispotition and bureaucratic structure. Of the four indicators used as analysis tools, it was found that the Implementation of the Complete Systematic Land Registration Program at the Land Office of Pelalawan Regency was quite good with several obstacles that emerged.